Трет-бутилацетилен и пропаргиловый спирт в реакциях с CH-кислотами - Ж. А. Чобанян (ՀՀ ԳԱԱ հրատ.)
Oсушествлено взаимодействие производных ацетилена с СН-кислотами. Трет-бутилацетилен реагирует с СН-кислотами в диоксане в присутствии ацетата ртути с образованием продуктов винилирования и производных кетонов в соотношении 1:6 (по ГЖХ). Замена диоксана на ДМСО и нагревание реакционной смеси приводят к исключительному получению производных кетонов. Реакция пропаргилового спирта с СН-кислотами приводит к образованию замещенных фуранов. Մշակվել է կետոնների ածանցյալների սինթեզ CH-թթուների և ացետիլենի ածանցյալների փոխազդեցության հիման վրա: Երրորդային բուտիլացետիլենի և CH-թթուների փոխազդեցությունը դիօքսանում` Hg(OAc)2 ներկայությամբ բերում է վինիլացման արգասիքների և կետոնների ածանցյալների առաջացմանը 1:6 հարաբերությամբ: Դիօքսանը փոխարինելով ԴՄՍՕ-ով և ռեակցիոն խառնուրդը տաքացնելով, իրականացվել է բացառապես զուգորդված կետոնային ածանցյալների սինթեզ: Պրոպարգիլ սպիրտը CH-թթուների հետ փոխազդելով առաջացնում է տեղակալված ֆուրաններ: New method for the synthesis of derivatives of ketones on the basis of CH-acids and acetylene derivatives has been elaborated. Interaction of tert-butylacetylene with CH-acids in dioxane in presence of Hg(OAc)2 provides vinylation products and derivatives of ketones in ratio 1:6 (by GLC). This may be explained by thermodynamic stability of derivatives of ketones due to conjugation of dicarbonyl system with α,β-double bond. Exceptional formation of derivatives of ketones is achieved by the change of dioxane by DMSO and heating of the reaction mixture. As was expected, propargyl alcohol not having structural limitation for further isomerization, as in case of tert-butylacetylene, easily interacts with CH-acids affording furane derivatives.
Keywords: Chemistry; Organic Chemistry